Research on the educational influence on schooling commitment impulse buying intention of educational leadership with the help of educational motivation, knowledge sharing and educational team effectiveness - Qiu, Huanhuan; Huang, Fei (Edelweiss Applied Science and Technology, 2025)
To explain the relationship between educational motivation, knowledge sharing, educational teams, and educational leadership. This research identifies the effects of educational motivation, knowledge sharing, and the effectiveness of educational teams on educational leadership and the mediating effects of educational commitment; it highlights the importance of educational leadership and school commitment and provides the data needed to enhance the educational capacity of faculty members. Data was collected from 400 faculty members of Chinese schools, colleges, and universities. This research was based on a non-probability sampling method that utilized convenience sampling to gather information from respondents. Smart-PLS has been used for analysis. The analysis of the data shows that educational motivation, knowledge sharing, and the effectiveness of educational teams have a significant and positive impact on educational leadership. The study is useful for educational institutes, faculty members, and students in understanding educational leadership by focusing on the aforementioned factors. Future studies can identify other factors that have a significant effect on the relationship between school commitment and educational leadership in any institute.